PENGARUH MODEL PEMBELAJARAN CPS TERHADAP KEMAMPUAN MATEMATIS KELAS XII SMA - Muskhir, Muhandisa (Jurnal Edukasi dan Penelitian Matematika, 2023)
This study aims to obtain the influence of the application of the Creative Problem Solving (CPS) method in the learning process at SMA Negeri 3 Padang. This method is measured based on four indicators, namely (1) understanding of the problem, (2) selecting a strategy, (3) solving the problem, and (4) re-examining the results of the answers. The four indicators are used to measure students' ability to solve non-routine questions. The CPS method is applied by making students the center of learning. The treatment given to the experimental class is to provide a way to understand the problem. Understanding of the questions asked by the problem and followed by choosing the right strategy and how to solve the problem. The final treatment is to provide skills to interpret the meaning contained in the answers given and compare them with the questions to be achieved. The research was conducted using a quasi-experimental methodology with The Static Group Comparison Design. The conclusion that can be drawn is that there is a significant effect of applying the CPS method, namely the average ability of students in the experimental class is 9.04 in the experimental class and 8.06 in the control class based on the maximum assessment reference is 12. The CPS method in this study shows more influence the learning process. Keywords– Creative, Problem, Solving, mathematic, prevalent.